2021
DOI: 10.1039/d0tc05563h
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructured plasmonic memristors with tunable opto-synaptic functionalities

Abstract: The N2 incorporation into an atomically-thin In2O3 film at Au/In2O3–TiO2 heterointerfaces enabled the synergistic improvement of the long-term plasticity (LTP) of artificial metal oxide optical synapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…At the device structure level, on the one hand, further understanding of the working mechanism of photoelectric memristors is needed. New optoelectronic device structures with continuous plasticity and high integration density should be explored to broaden the application scenarios of optoelectronic memristors and expand their applications in the field of artificial intelligence. , On the other hand, it is necessary not only to further apply photoelectric modulation to devices to obtain more conductive states but also to develop visual perception systems and more deeply simulate the complex functions of the brain, providing new opportunities for advanced machine vision systems. , The future development diagram of photoelectric memristor-based machine vision is shown in Figure . It is believed that with the efforts of researchers, photoelectric memristor-based machine vision will achieve significant breakthroughs in the application of artificial intelligence in the near future. Research regarding machine vision systems based on photoelectric memristors is a multidisciplinary research field closely related to artificial intelligence and has become an important strategic research topic in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the device structure level, on the one hand, further understanding of the working mechanism of photoelectric memristors is needed. New optoelectronic device structures with continuous plasticity and high integration density should be explored to broaden the application scenarios of optoelectronic memristors and expand their applications in the field of artificial intelligence. , On the other hand, it is necessary not only to further apply photoelectric modulation to devices to obtain more conductive states but also to develop visual perception systems and more deeply simulate the complex functions of the brain, providing new opportunities for advanced machine vision systems. , The future development diagram of photoelectric memristor-based machine vision is shown in Figure . It is believed that with the efforts of researchers, photoelectric memristor-based machine vision will achieve significant breakthroughs in the application of artificial intelligence in the near future. Research regarding machine vision systems based on photoelectric memristors is a multidisciplinary research field closely related to artificial intelligence and has become an important strategic research topic in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…New optoelectronic device structures with continuous plasticity and high integration density should be explored to broaden the application scenarios of optoelectronic memristors and expand their applications in the field of artificial intelligence. 117,118 On the other hand, it is necessary not only to further apply photoelectric modulation to devices to obtain more conductive states but also to develop visual perception systems and more deeply simulate the complex functions of the brain, providing new opportunities for advanced machine vision systems. 119,120 The future development diagram of photoelectric memristor-based machine vision is shown in Figure 16.…”
Section: Discussionmentioning
confidence: 99%
“…However, the surface oxide of galinstan is composed of Ga 2 O 3 . Since the Δ G f of Ga 2 O 3 is lower than that of In 2 O 3 and SnO 2 in oxygen atmosphere, the surface oxide of galinstan alloy is mostly composed of Ga 2 O 3 [ 155 ]. With the same synthesis strategy, it is possible to synthesize the mixed 2D oxide films similar indium–tin–oxide.…”
Section: D Nanomaterials Synthesized By Vapor-based Fabrication Techniquesmentioning
confidence: 99%
“…Note that titanium oxide (TiO x ) has been well studied as candidate of memristor to construct articial synapses. [14][15][16] The migration and diffusion process of oxygen ions enable the modulation of electrical conductance, thus allowing the mimicking of synaptic functions of biology neurons, such as short-term plasticity (STP), long-term plasticity (LTP), pulse-paired facilitation (PPF), 17,18 etc. Previous studies have revealed the feasibility of controllably oxidization technique to create 2D oxide and related heterostructures, 19,20 thus it is expected that TiO x and related heterostructures can also be achieved in 2D conguration based on 2D TiS 3 nanosheets.…”
Section: Introductionmentioning
confidence: 99%